2022
DOI: 10.1080/21655979.2022.2070963
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid A (Sal A) suppresses malignant progression of glioma and enhances temozolomide (TMZ) sensitivity via repressing transgelin-2 (TAGLN2) mediated phosphatidylinositol-3-kinase (PI3K) / protein kinase B (Akt) pathway

Abstract: Glioma originated from excessively proliferative and highly invaded glial cells is a common intracranial malignant tumor with poor prognosis. Resistance to temozolomide (TMZ) is a clinical challenge in glioma treatment due to the fact that chemoresistance remains a main obstacle in the improvement of drug efficacy. Salvianolic acid A (Sal A), originated from traditional Chinese herbal medicine Salvia miltiorrhiza , possesses anti-tumor effects and could facilitate the delivery of drugs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…However, not all patients respond to TMZ ( 30 , 31 ). It was previously reported that PI3K/AKT axis inhibitors could inhibit temozolomide resistance in glioblastoma cells ( 32 34 ), and activation of the PI3K/AKT axis could promote TMZ resistance in GBM cells ( 35 37 ). Therefore, we suspect that safranal and TMZ may have a synergistic effect against GBM.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all patients respond to TMZ ( 30 , 31 ). It was previously reported that PI3K/AKT axis inhibitors could inhibit temozolomide resistance in glioblastoma cells ( 32 34 ), and activation of the PI3K/AKT axis could promote TMZ resistance in GBM cells ( 35 37 ). Therefore, we suspect that safranal and TMZ may have a synergistic effect against GBM.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] Studies have shown that TAGLN2 is induced in the hypoxic microenvironment of glioblastoma PDX cell lines, and it enhances cellular resistance to standard treatments by binding and inhibiting PTEN, thus activating the PI3K/Akt pathway. [ 29 ] Danphenolic acid F inhibits the growth of KRAS-dependent lung cancer cells via the PI3K/AKT signaling pathway. [ 30 ] ERK is a key member of the MAPK family.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, RGS16, CLEC5A and TAGLN2 are key regulatory factors that promote glioma progression by activating the PI3K-AKT pathway in gliomas. [53][54][55][56] Additionally, upregulated STEAP3 in gliomas facilitates tumour cell migration and invasion and is significantly associated with immune-infiltrating cells, including macrophages and neutrophils, particularly M2 macrophages. 57 Furthermore, the highly expressed CHI3L1 in gliomas enhances NF-κB signalling by facilitating the translocation of NF-κB subunits through binding to ACTN4…”
Section: Discussionmentioning
confidence: 99%
“…Notably, EMP3, RGS16, PLAU, TAGLN2, STEAP3, CDHR1, OSMR, SERPINH1, PDPN, CHI3L1, ABCC3, SERPINE1, SOCS1, GPX8, GPNMB, CLEC5A, FOSL2, ICAM1, PRF1 and ITPRIP serve as prognostic markers for gliomas 9,41–52 . Among them, RGS16, CLEC5A and TAGLN2 are key regulatory factors that promote glioma progression by activating the PI3K‐AKT pathway in gliomas 53–56 . Additionally, upregulated STEAP3 in gliomas facilitates tumour cell migration and invasion and is significantly associated with immune‐infiltrating cells, including macrophages and neutrophils, particularly M2 macrophages 57 .…”
Section: Discussionmentioning
confidence: 99%